2017
DOI: 10.2174/1876386301710010029
|View full text |Cite
|
Sign up to set email alerts
|

Study of Evaluation of Symptoms of Juvenile Recurrent Parotitis Prior to and After Sialendoscopy

Abstract: Abstract:Background:

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…A small minority of cases underwent instrumentation such as balloon dilation or microdrilling (136 sialoendoscopies) [ 1 , 9 , 11 , 14 , 20 , 30 ]. Combined corticosteroid and antibiotic irrigation was performed in 16.3% of the sialoendoscopies (105 techniques) [ 7 , 22 , 30 ] and the exclusive use of saline lavage in 2% of the procedures [ 18 , 31 ]. The percentage of recurrences according to the type of ductal irrigation used ranged from 22.2% to 25.2%, with no significant differences between the use of corticosteroids alone (25.2% of recurrences), corticosteroids plus antibiotics (25% of recurrences) or saline alone (22.2% of recurrences) (Additional file 1 : Table s2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A small minority of cases underwent instrumentation such as balloon dilation or microdrilling (136 sialoendoscopies) [ 1 , 9 , 11 , 14 , 20 , 30 ]. Combined corticosteroid and antibiotic irrigation was performed in 16.3% of the sialoendoscopies (105 techniques) [ 7 , 22 , 30 ] and the exclusive use of saline lavage in 2% of the procedures [ 18 , 31 ]. The percentage of recurrences according to the type of ductal irrigation used ranged from 22.2% to 25.2%, with no significant differences between the use of corticosteroids alone (25.2% of recurrences), corticosteroids plus antibiotics (25% of recurrences) or saline alone (22.2% of recurrences) (Additional file 1 : Table s2).…”
Section: Resultsmentioning
confidence: 99%
“…The complications described are: swelling and pain [ 15 , 25 , 30 , 35 ], duct perforation [ 7 , 20 ], proximal duct stenosis [ 24 ], rare cases of upper airway obstruction [ 20 , 26 ], and the usual risks of general anesthesia [ 11 ]. In 95.6% of the patients there were no complications or this data was not available [ 1 , 17 , 18 , 22 , 23 , 28 , 29 , 32 , 36 ].…”
Section: Resultsmentioning
confidence: 99%
“…This study showed that DCI alone can treat JRP patients and showed similar results as sialoendoscopy along with corticosteroid, indicating that it was the application of corticosteroids that caused the improvement in the disease symptoms [ 21 ]. Faizal et al in their study of 22 patients found that sialoendoscopy showed better results in these patients who were managed medically prior to salivary endoscopy in terms of pain scores and longer remission time (Table 1 ) [ 22 ].…”
Section: Discussionmentioning
confidence: 99%